Effectiveness of the fraud triangle model in the detection of financial statement fraud in South African municipalities - Ambani Tshikovhi; Emmanuel K. Oseifuah; Arthur Reynolds (Public and Municipal Finance, 2025)
There is a high prevalence of financial statement fraud and wasteful expenditure in South African municipalities. According to the fraud triangle model, pressure, opportunity, and rationalization are the underlying causes of financial statement fraud. The study aimed to examine the effectiveness of the fraud triangle model in detecting financial statement fraud in South African municipalities. The study developed variables serving proxy measures for pressure, opportunity, and rationalization. The variables were analyzed and tested using the logistics regression model and publicly available financial data for the 257 municipalities in South Africa over six years, from 2015/16 to 2020/21. The results showed a high correlation between fraud in financial statements and four fraud risk markers. High capital expenditure, high accrual amounts, poor liquidity ratios, and high leverage ratios are the risk elements. The results contribute fresh perspectives to the corpus of information already available on financial statement fraud in South Africa. To ascertain the effectiveness of the fraud triangle model in identifying and preventing financial statement fraud, future studies should incorporate different range of variables, techniques, and sample sizes.